Supporting good traditions - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Namo Chuma, of the NGO Environment Africa, explains how traditional arrangements have protected trees in Zimbabwe, and how a new piece of legislation could empower communities to protect their forests against illegal exploitation by commercial interests.